Synthesis of flexible polymeric shielding materials for soft gamma rays: Physicomechanical and attenuation characteristics of radiation crosslinked polydimethylsiloxane/Bi2O3 composites. Issue 3 (18th September 2014) - Dubey, K.A.; Chaudhari, C.V.; Suman, S.K.; Raje, N.; Mondal, R.K.; Grover, V.; Murali, S.; Bhardwaj, Y.K.; Varshney, L.
Abstract : Flexible lead‐free high energy radiation shielding material was developed through internal compounding. Polymer‐filler interaction, crosslinking density, specific gravity, physicomechanical characteristics, percentage attenuation, and thermal stability of the crosslinked composites were estimated. It was found that even at very high filler loading composites can be crosslinked; however, the crosslinking density was composition dependent and was highest in 10–50 wt% loading range at 100 kGy and 200 kGy. The Nielsen model was applied to understand the micromechanics of the system. Attenuation of gamma radiation from Am241 was not affected by the crosslinking density. Thermal stability of the composites was found to be significantly affected with bismuth oxide loading. POLYM. COMPOS., 37:756–762, 2016. © 2014 Society of Plastics Engineers